Implementation of Surakarta City Regional Regulation Number 7 of 2023 towards Fulfillment of the Rights to Housing and Settlement Areas in Surakarta City - Farras Hibban; Adriana Grahani Firdausy (PT ARRUS Intelektual Indonesia, 2024)
This study aims to determine and analyze the implementation of Surakarta City Regional Regulation Number 7 of 2023 concerning the Implementation of Housing and Settlement Areas and to determine and analyze the challenges and obstacles faced by the Surakarta City Government in fulfilling the right to housing and settlement areas in Surakarta City. The research method used is a non-doctrinal research method or empirical research using descriptive research. The approach used is a qualitative approach. The types of data used are primary and secondary data. Primary data collection techniques through interviews with related parties to examine the problems that occur while secondary data through literature studies in the form of official documents or books. The results showed that the implementation of Surakarta City Regional Regulation Number 7 of 2023 concerning the Implementation of Housing and Settlement Areas has not fully reflected the fulfillment of the right to housing and residential areas as evidenced by the fact that there are still illegal settlements whose ownership legality is still not guaranteed. The cause of the unfulfillment of the right to housing and residential areas is the limited land in Surakarta City which is increasingly limited while the need for housing is increasing and the price of land is increasing as well as the limited budget of the Surakarta City Government to meet the housing needs of residents who are still affected by illegal settlements and residents' awareness of maintaining settlements so that they do not return to slums after the instrument from the government. Therefore, there needs to be a deep seriousness given by the Surakarta City Government regarding the implementation of Surakarta City Regional Regulation Number 7 of 2023 concerning the Implementation of Housing and Settlement Areas in order to uphold the fulfillment of rights for low-income people and people affected by illegal settlements.